Visualization of viscoplastic fluid flow in an abrupt contraction using particle image velocimetry - Garcia Blanco, Yamid Jose (2019)
The viscoplastic fluid flow of Carbopol solutions is investigated in the following experimental study, for laminar and turbulent regime through an abrupt contraction with an aspect ratio of β = 1:85. The pressure drop profile and the pressure drop coefficient at the contraction are obtained for different entrance Reynolds numbers, Re0D. The velocity vector fields are obtained for Re0 D between 1 and 10 000, using the Particle Image Velocimetry (PIV-2D). Mean velocity vector field and first-order turbulent quantities such as radial and axial velocity fluctuations are obtained, as well as centerline velocity behavior, vortex structures, and visualization of unyielded regions. It is observed that the pressure drop coefficient for viscoplastic fluid flow is dependent on the Re0D for the laminar regime, and reaches a constant value for turbulent conditions, exhibiting good agreement with data available on the literature. The velocity profiles along the test section present lower values than those obtained for Newtonian fluids in both regimes and vary their behavior according to the rheological properties for each viscoplastic solution. Besides, the turbulent fluctuations approach the Newtonian behavior, with a slight difference for the radial profiles. The unyielded regions are deformed as the Reynolds number is increased and are replaced by vortex structures as the flow reaches transitional conditions, obtaining a variation of the effective diameter at the entrance of the contraction. The growth and changes of the vortex structure are studied using quantitative techniques based on the strain rate and the vorticity tensors, to gain accurate and better information about the behavior for these structures into the viscoplastic fluid flow. Finally, a relation was found for the entrance Reynolds number and the Reynolds number at the contraction plane, which is not dependent on the rheological parameters due to the high shear rates in this region.